2020
DOI: 10.1111/micc.12620
|View full text |Cite
|
Sign up to set email alerts
|

Sigma‐1 receptor activation‐induced glycolytic ATP production and endothelial barrier enhancement

Abstract: The σ1 is a single 25-kDa transmembrane protein residing primarily in the ER that acts as a chaperone protein. Its interaction with mitochondria at the mitochondria-associated ER membrane domain is well documented. 1 Following activation, σ1 has been reported to bind to the IP 3 R, and modulate intracellular calcium homeostasis. 2 Also, the activated σ1 modulates plasma membrane receptors and ion channel functions, and may regulate cellular excitability. 3-6 Further, σ1 affects trafficking of lipids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Our data were further substantiated when EC barrier disruption caused by human septic plasma was protected in the presence of PRE-084. These observations are in line with earlier studies in human dermal lymphatic endothelial cells (HDLECs) and human umbilical vein endothelial cells (HUVECs), where Sig1R is shown to be protective against endothelial barrier disruption through its ability to enhance glycolytic energy production [ 52 , 53 ]. Furthermore, since Ca 2+ plays a critical role in intracellular signaling and is a critical mediator of EC permeability, we also tested the ability of Sigma1R to control Ca 2+ signaling in EC.…”
Section: Discussionsupporting
confidence: 89%
“…Our data were further substantiated when EC barrier disruption caused by human septic plasma was protected in the presence of PRE-084. These observations are in line with earlier studies in human dermal lymphatic endothelial cells (HDLECs) and human umbilical vein endothelial cells (HUVECs), where Sig1R is shown to be protective against endothelial barrier disruption through its ability to enhance glycolytic energy production [ 52 , 53 ]. Furthermore, since Ca 2+ plays a critical role in intracellular signaling and is a critical mediator of EC permeability, we also tested the ability of Sigma1R to control Ca 2+ signaling in EC.…”
Section: Discussionsupporting
confidence: 89%
“…Although thought to be specific to the σ1R, a study has shown that it can have some off-target effects. PRE-084 could elicit an enhanced barrier function of human umbilical vein endothelial cell (HUVEC) monolayers in a dose-dependent fashion, and even with significant siRNA knockdown of the σ1R, PRE-084 maintained the barrier function effect, meaning that either only a low occupancy of σ1R is required for the barrier function effect, or that another receptor is involved [ 385 ].…”
Section: Sigma Receptor Ligands For Neurological Diseasementioning
confidence: 99%
“…However, it has also been suggested that Afobazole-induced NO-independent effects, as afobazole treatment in the presence of NOS inhibitor L-NAME led to a decrease in the normalized end-diastolic diameter of the isolated lymphatic vessel ( Trujillo et al, 2017 ). Recently, Sigmar1’s role in lymphatic endothelial barrier function has been demonstrated by a study showing the contribution of Sigmar1 to basal lymphatic endothelial barrier function, potentially through the enhancement of glycolytic energy production in cultured adult human dermal lymphatic endothelial cells ( Motawe et al, 2020 ). Despite all these pharmacologic data collected using non-selective ligands, the molecular role of Sigmar1 in the pathophysiology associated with the lymphatic system remains unknown.…”
Section: Physiological and Pathological Role Of Sigmar1mentioning
confidence: 99%